\documentclass[12pt]{article}
\usepackage{amsfonts,amssymb}
\usepackage{amsmath}
%\documentstyle[12pt,amsfonts]{article}
%\documentstyle{article}
\setlength{\topmargin}{-.5in}
\setlength{\oddsidemargin}{0 in}
\setlength{\evensidemargin}{0 in}
\setlength{\textwidth}{6.5truein}
\setlength{\textheight}{8.5truein}
%\input ../basicmath/basicmathmac.tex
%
%\input ../adgeomcs/lamacb.tex
\input {"./mac.tex"}
\input {"./mathmac.tex"}
\input {"./prooftree.tex"}
\def\qleq{\sqsubseteq}
\def\impl{\Rightarrow}
\def\falsum{\perp}
%
\begin{document}
\begin{flushright}
Alina Chin \& Di Mu\\[10pt]
\end{flushright}
\begin{center}
\fbox{{\Large\bf Fall 2010 \hspace*{0.4cm} CIS 160}}\\
\vspace{1cm}
{\Large\bf Mathematical Foundations of Computer Science\\
Jean Gallier \\
\vspace{0.5cm}
Homework 2}\\[10pt]
September 28, 2010; Due October 5, 2010\\
Beginning of class
\end{center}
\vspace {0.5cm}\noindent
{\bf Problem 1.}
(a) Prove the ``de Morgan'' laws in classical logic:
\begin{align*}
\neg(P \land Q) & \equiv \neg P \lor \neg Q \\
\neg(P \lor Q) & \equiv \neg P \land \neg Q.
\end{align*}
\settree1{
\starttree{$\neg (\neg P\lor \neg Q)^z$}
}
\settree2{
\starttree{$\neg P^\alpha $}
\step{$\neg P\lor \neg Q$}
}
\settree1{
\vnjointrees{1}{2}
\step{$\perp $}
\jstep{$P$}{$\scriptstyle \alpha$(by-contra)}
}
\settree3{
\starttree{$\neg (\neg P\lor \neg Q)^z$}
}
\settree4{
\starttree{$\neg Q^\beta$}
\step{$\neg P\lor \neg Q$}
}
\settree3{
\vnjointrees{3}{4}
\step{$\perp$}
\jstep{$Q$}{$\scriptstyle \beta$(by-contra)}
}
\settree1{
\njointrees{1}{3}
\step{$P\land Q$}
}
\settree5{
\starttree{$\neg (P\land Q)^w$}}
\settree1{
\vnjointrees{5}{1}
\step{$\falsum$}
\jstep{$\neg P\lor \neg Q$}{$\scriptstyle z$(by-contra)}
\jstep{$\neg(P \land Q) \impl \neg P \lor \neg Q$}{$\scriptstyle w$}
}
\bigskip
\ligne{\hfill\box1\hfill}
\settree1{
\starttree{$(P \land Q)^x$}
\step{$P$}
}
\settree3{
\starttree{$(P\land Q)^x$}
\step{$Q$}
}
\settree2{
\starttree{$(\neg Q)^w$}
}
\settree2{
\snjointrees{2}{3}
\step{$\falsum$}
\step{$\neg P$}
}
\settree3{
\starttree{$(\neg P \lor \neg Q)^y$}
}
\settree4{
\starttree{$(\neg P)^v$}
\step{$\neg P$}
}
\settree2{
\tnjointrees{3}{4}{2}
\jstep{$\neg P$}{$\scriptstyle v,w$}
}
\settree1{
\njointrees{1}{2}
\step{$\falsum$}
\jstep{$\neg (P \land Q)$}{$\scriptstyle x$}
\jstep{$(\neg P \lor \neg Q) \impl \neg (P \land Q)$}{$\scriptstyle y$}
}
\bigskip
\ligne{\hfill\box1\hfill}
\bigskip
\settree1{
\starttree{$(\neg (P \lor Q))^z$}
}
\settree2{
\starttree{$P^x$}
\step{$P \lor Q$}
}
\settree1{
\njointrees{1}{2}
\step{$\falsum$}
\jstep{$\neg P$}{$\scriptstyle x$}
}
\settree2{
\starttree{$(\neg (P \lor Q))^z$}
}
\settree3{
\starttree{$Q^x$}
\step{$P \lor Q$}
}
\settree2{
\njointrees{2}{3}
\step{$\falsum$}
\jstep{$\neg Q$}{$\scriptstyle y$}
}
\settree1{
\njointrees{1}{2}
\step{$\neg P \land \neg Q$}
\jstep{$\neg (P \lor Q) \impl (\neg P \land \neg Q)$}{$\scriptstyle z$}
}
\bigskip
\ligne{\hfill\box1\hfill}
\bigskip
\settree1{
\starttree{$(\neg P \land \neg Q)^w$}
\step{$\neg Q$}
}
\settree2{
\starttree{$Q^y$}
}
\settree3{
\snjointrees{2}{1}
\step{$\falsum$}
\step{$P$}
}
\settree2{
\starttree{$P^x$}
\step{$P$}
}
\settree1{
\starttree{$(P \lor Q)^z$}
}
\settree1{
\tnjointrees{1}{2}{3}
\jstep{$P$}{$\scriptstyle x, y$}
}
\settree2{
\starttree{$(\neg P \land \neg Q)^w$}
\step{$\neg P$}
}
\settree1{
\njointrees{2}{1}
\jstep{$\falsum$}{$\scriptstyle z$ ($\neg$-intro)}
\step{$\neg (P \lor Q)$}
\jstep{$(\neg P \land \neg Q) \impl \neg (P \lor Q)$}{$\scriptstyle w$}
}
\bigskip
\ligne{\hfill\box1\hfill}
\medskip
(b)
Prove that $\neg(P \lor Q) \equiv \neg P \land \neg Q$ is also provable
in intuitionistic logic.
We proved $\neg(P \lor Q) \equiv \neg P \land \neg Q$ without RAA in part a, so it can be seen as intuitionistic logic too.
\medskip
(c)
Prove that the proposition $(P \land \neg Q) \impl \neg(P \impl Q)$ is provable
in intuitionistic logic and
$\neg(P \impl Q) \impl (P \land \neg Q)$ is provable in
classical logic.
\settree1{
\starttree{$(P \land \neg Q)^x$}
\step{$P$}
}
\settree2{
\starttree{$(P \impl Q)^y$}
}
\settree2{
\njointrees{1}{2}
\step{$Q$}
}
\settree1{
\starttree{$(P \land \neg Q)^x$}
\step{$\neg Q$}
}
\settree1{
\njointrees{1}{2}
\step{$\falsum$}
\jstep{$\neg (P \impl Q)$}{$\scriptstyle y$ ($\neg$-intro)}
\jstep{$(P \land \neg Q) \impl \neg (P \impl Q)$}{$\scriptstyle x$}
}
\bigskip
\ligne{\hfill\box1\hfill}
\settree1{
\starttree{$\neg (P\impl Q)^x$}
}
\settree2{
\starttree{$Q^z$,$P^\alpha$}
\step{$Q$}
\jstep{$P \impl Q$}{$\scriptstyle \alpha$}
}
\settree1{
\vnjointrees{1}{2}
\step{$\perp$}
\step{$P$}
}
\settree3{
\starttree{$\neg (P\impl Q)^x$}
}
\settree4{
\starttree{$Q^z$,$P^\beta$}
\step{$Q$}
\jstep{$P\impl Q$}{$\scriptstyle \beta$}
}
\settree3{
\vnjointrees{3}{4}
\step{$\perp$}
\step{$\neg Q$}
}
\settree1{
\vnjointrees{1}{3}
\step{$P\land \neg Q$}
\jstep{$\neg(P \impl Q) \impl (P \land \neg Q)$}{$\scriptstyle x$}
}
\bigskip
\ligne{\hfill\box1\hfill}
\medskip
\vspace {0.5cm}\noindent
{\bf Problem 2.}
(a) Prove that $P \impl \neg\neg P$ is provable in intuitionistic logic.
\settree1{
\starttree{$P^x$, $(P\impl \perp)^y$}
\step{$\falsum$}
\jstep{$(P\impl \perp)\impl \perp$}{$\scriptstyle y$}
\jstep{$P\impl ((P\impl \perp)\impl \perp)$}{$\scriptstyle x$}
}
\bigskip
\ligne{\hfill\box1\hfill}
\medskip
(b)
Prove that $\neg\neg\neg P$ and $\neg P$ are
equivalent in intuitionistic logic.
\settree1{
\starttree{$\neg ((P\impl \perp)\impl \perp)^y$}
}
\settree2{
\starttree{$P^y$,$(P \impl \perp)^z$}
\step{$\perp$}
\step{$((P\impl \perp)\impl \perp)^z$}
}
\settree1{
\vnjointrees{1}{2}
\step{$\perp$}
\jstep{$P\impl \perp$}{$\scriptstyle y$}
\jstep{$((P\impl \perp)\impl \perp)\impl (P\impl \perp)$}{$\scriptstyle x$}
}
\bigskip
\ligne{\hfill\box1\hfill}
\settree1{
\starttree{$((P\impl \perp)\impl \perp)^y$, $(P\impl \perp)^x$}
\step{$\perp$}
\jstep{$((P\impl \perp)\impl \perp)\impl \perp$}{$\scriptstyle y$}
\jstep{$(P\impl \perp)\impl (((P\impl \perp)\impl \perp)\impl \perp)$}{$\scriptstyle x$}
}
\bigskip
\ligne{\hfill\box1\hfill}
\vspace {0.5cm}\noindent
{\bf Problem 3}
(a)
Prove that the proposition
\[
(P \lor \neg P) \impl (((P \impl Q) \impl P) \impl P)
\]
is provable in intuitionistic logic.
\settree1{
\starttree{$((P\impl Q)\impl P)^\alpha $}
}
\settree2{
\starttree{$\neg P^y$, $P^y$}
\step{$\perp$}
\step{$Q$}
\jstep{$P\impl Q$}{$\scriptstyle x$}
}
\settree1{
\vnjointrees{1}{2}
\step{$P$}
\jstep{$((P\impl Q)\impl P)\impl P$}{$\scriptstyle \alpha$}
}
\settree3{
\starttree{$((P\impl Q)\impl P)^\beta$, $P^x$}
\step{$P$}
\jstep{$((P\impl Q)\impl P)\impl P$}{$\scriptstyle \beta $}
}
\settree4{
\starttree{$(P\lor \neg P)^t$}
}
\settree1{
\tjointrees{1}{3}{4}
\jstep{$((P\impl Q)\impl P)\impl P$}{$\scriptstyle x,y$}
\jstep{$(P \lor \neg P) \impl (((P \impl Q) \impl P) \impl P)$}{$\scriptstyle t$}
}
\bigskip
\ligne{\hfill\box1\hfill}
\medskip
(b)
Prove that the proposition
$((P \impl Q) \impl P) \impl P$ is classically provable.
\settree1{
\starttree{$((P\impl Q)\impl P)^x$}
}
\settree2{
\starttree{$(\neg P^)y$, $P^y$}
\step{$\falsum$}
\step{$Q$}
\jstep{$P\impl Q$}{$\scriptstyle x$}
}
\settree1{
\vnjointrees{1}{2}
\step{P}
}
\settree3{
\starttree{$(\neg P)^y$}
}
\settree1{
\jointrees{1}{3}
\step{$\falsum$}
\jstep{$P$}{$\scriptstyle y (RAA)$}
\jstep{$((P \impl Q) \impl P) \impl P$}{$\scriptstyle x$}
}
\bigskip
\ligne{\hfill\box1\hfill}
\vspace {0.5cm}\noindent
{\bf Problem 4}
(a)
Prove that the proposition
\[
\neg\neg (((P \impl Q) \impl P) \impl P)
\]
is provable in intuitionistic logic.
\medskip
(b)
Use (a) to prove that the proposition
$((P \impl Q) \impl P) \impl P$ is classically provable.
\vspace {0.5cm}\noindent
{\bf Problem 5.}
Prove that the rule
\settree1{
\starttree{$\Gamma$}
\istep{$\s{D}_1$}
\istep{$P\impl Q$}
}
\settree2{
\starttree{$\Delta$}
\istep{$\s{D}_2$}
\istep{$\neg Q$}
}
\settree1{
\njointrees{1}{2}
\step{$\neg P$}
}
\bigskip
\ligne{\hfill\box1\hfill}
\bigskip\noindent
can be derived from the other rules of intuitionistic logic.
This means that you have to describe how a deduction tree $\s{D}_1$ for
$P \impl Q$ from $\Gamma$ and a deduction tree $\s{D}_2$ for
$\neg Q$ from $\Delta$ can be combined to obtain a deduction
of $\neg P$ from $\Gamma\cup \Delta$.
\end{document}